Single‐Cell Nanoencapsulation of Saccharomyces cerevisiae by Cytocompatible Layer‐by‐Layer Assembly of Eggshell Membrane Hydrolysate and Tannic Acid. Issue 1 (8th December 2020) - Han, Sang Yeong; Lee, Hojae; Nguyen, Duc Tai; Yun, Gyeongwon; Kim, Seulbi; Park, Ji Hun; Choi, Insung S.
Abstract : Single‐cell nanoencapsulation (SCNE) demands cytocompatible materials and processes to ensure the maintenance of cell viability and prefers the degradation‐on‐demand and postfunctionalization of the cytoprotective shells. Although the layer‐by‐layer (LbL) method has intensively been used for SCNE, there have been few reports on the cytocompatible LbL shells that are postfunctionalizable under mild conditions. Herein, the use of nature‐derived eggshell membrane hydrolysate (ESMH) as a counter component to tannic acid (TA) for hydrogen bonding‐based LbL shell formation on Saccharomyces cerevisiae is proposed. In addition to the great cytocompatibility of the LbL process and protective capability of the ESMH/TA shell (e.g., 18‐fold increase in survival against Cu 2+ ), the shell is postfunctionalizable, benefitting from the presence of various functional groups in the ESMH, as demonstrated by reactions with N ‐hydroxysuccinimide‐ or maleimide‐conjugated fluorescent probes and bioinspired silicification. This work suggests that ESMH would be an advanced biomaterial for chemically interfacing with living cells in a controlled fashion. Abstract : The eggshell membrane hydrolysate (ESMH) is used for hydrogen bonding‐based layer‐by‐layer (LbL) shell formation, with tannic acid (TA), on individual Saccharomyces cerevisiae in single‐cell nanoencapsulation. The cytocompatible ESMH/TA shell is cytoprotective, degradable, and postfunctionalizable, fulfilling the basic shell requirement for artificial spores.